Nitrogen Fixation by Leucaena leucocephala as Measured by N-15 Dilution Technique - Abdul Rahman, Zaharah; Abdul Hamid, Sharifuddin; Subramaniam, R. (1986)
A field trial was conducted to measure the amount of nitrogen fixed by Leucaena leucocephala using the isotope dilution technique proposed by Fried and Broeshart (1975). Three varieties of Leucaena (A ccession 55/65, Cunningham and Peruvian) were planted both as a sole crop and mixed with Setaria anceps var. splendida grass. It was found that Leucaena can fix up to 78% of the nitrogen present in the plant tops within the period of three months. Le(caena grown as a sole crop tends to fix more nitrogen than those grown mixed with the grass.